THE EFFECT OF CASH FLOWS, ACCOUNTING PROFIT, AND NET PROFIT MARGIN ON SHARE RETURN: A STUDY AT TELECOMMUNICATION COMPANIES LISTED IN INDONESIA STOCK EXCHANGE 2009-2014 - Rochmatullah Eka Salvega (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study aimed to determine whether there was significant effect changes of cash flows, accounting profit, and net profit margin toward share return. This study used a sample of five telecommunication companies listed on the Indonesia Stock Exchange (BEI), which were selected using purposive sampling technique. The data used in this research was secondary data obtained from annual financial statements published in the Indonesia Stock Exchange from 2009-2014. The results revealed that accounting profit have significant effect on share returns partially. Meanwhile, cash flow, and net profit margin do not have a significant effect on share return partially. The results also showed that the cash flows, accounting profit, and net profit margin simultaneously have a significant effect on share returns.Keywords: Cash Flow, Accounting Profit, Net Profit Margin, Share Return, Investment Decision